2017
DOI: 10.1038/srep40818
|View full text |Cite
|
Sign up to set email alerts
|

Global mapping of nonseismic sea level oscillations at tsunami timescales

Abstract: Present investigations of sea level extremes are based on hourly data measured at coastal tide gauges. The use of hourly data restricts existing global and regional analyses to periods larger than 2 h. However, a number of processes occur at minute timescales, of which the most ruinous are tsunamis. Meteotsunamis, hazardous nonseismic waves that occur at tsunami timescales over limited regions, may also locally dominate sea level extremes. Here, we show that nonseismic sea level oscillations at tsunami timesca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 34 publications
2
39
0
2
Order By: Relevance
“…Finally, even though the seiches of the eastern Caribbean are smaller than those reported in some other parts of the world (and the currents associated with them will also be small), it has been shown that they can be as large as 10s cm in places. Therefore, as Vilibić and Šepić (2017) have remarked in the context of high frequency sea level variability in general, they should be taken into account when extreme levels are calculated for coastal engineers. Even if there is a 'continuous seiche', for which the forcing may not be understood perfectly, then it should be possible to combine the statistics of seiche variability with the extreme levels determined by conventional analysis of hourly data into better estimates of sea level return probabilities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, even though the seiches of the eastern Caribbean are smaller than those reported in some other parts of the world (and the currents associated with them will also be small), it has been shown that they can be as large as 10s cm in places. Therefore, as Vilibić and Šepić (2017) have remarked in the context of high frequency sea level variability in general, they should be taken into account when extreme levels are calculated for coastal engineers. Even if there is a 'continuous seiche', for which the forcing may not be understood perfectly, then it should be possible to combine the statistics of seiche variability with the extreme levels determined by conventional analysis of hourly data into better estimates of sea level return probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Its data archive was not intended to be a resource for scientific research, although some investigators of sea level variability have taken advantage of it (e.g. Vilibić and Šepić 2017).…”
Section: Data Setsmentioning
confidence: 99%
See 3 more Smart Citations